Impact of Household Social Factors on Stunting among Under-Five Children in a Public Health Center: A Cross-Sectional Study - Apripan, Rika; Rosmainun, Rosmainun; Permayasa, Nayodi (Chakra Brahmanda Lentera Institute, 2026)
Background: Stunting is a chronic growth disorder in young children characterized by height below age standards and is closely linked to household social conditions. Factors such as parenting practices, maternal education, employment, and family socioeconomic status are believed to influence stunting. However, evidence remains limited regarding which household-level social determinants exert the strongest influence on stunting within primary healthcare settings in Indonesia. This study aimed to analyze the impact of household social factors on stunting among children under five. Methods: This research employed an observational study with a cross-sectional design. A total of 215 mothers with children under five were selected from a population of 466 using purposive sampling. Data were collected through structured questionnaires. Statistical analysis was conducted using chi-square tests to examine associations and logistic regression to determine the most influential factors. Results: The findings revealed significant associations between stunting and parenting practice (p = 0.001), maternal education level (p = 0.002), family income (p = 0.001), and complementary feeding practices (p = 0.001). Logistic regression analysis indicated that complementary feeding practices were the most dominant factor influencing stunting, with an Exp(B) value of 12.927. Conclusion: Stunting among children under five is significantly influenced by household social factors, particularly complementary feeding practices, which play the most critical role. Strengthening nutrition education, promoting appropriate complementary feeding, and enhancing family support programs are strongly recommended to reduce stunting prevalence in the community.